1998
DOI: 10.1021/es980107a
|View full text |Cite
|
Sign up to set email alerts
|

Dry Deposition of Particulate Polychlorinated Biphenyls and Polycyclic Aromatic Hydrocarbons to Lake Michigan

Abstract: Dry deposition was collected from November 1993 to October 1995 at multiple sites within the Lake Michigan basin to estimate fluxes of particulate polychlorinated biphenyls (PCBs) and polycyclic aromatic hydrocarbons (PAHs) as part of the Lake Michigan Mass Balance Study (LMMBS). Samples were also collected during the Atmospheric Exchange over Lakes and Oceans (AEOLOS) project to estimate fluxes to coastal waters adjacent to the Chicago urban area. Fluxes of particulate PCBs and PAHs were higher in Chicago tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
85
2
8

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(109 citation statements)
references
References 57 publications
14
85
2
8
Order By: Relevance
“…The PAH levels at the urban site determined in this study are comparable to those reported by Possanzini et al [30] for downtown Rome and by Halsall et al [31] for urban sites in London and Manchester. Because of their higher volatility, low to medium molecular weight PAHs (3-5 rings) were more abundant in the gas-phase in the present study, similar to the previous studies [24,[32][33][34]. Higher ambient PAH concentrations were measured in the gasphase and 14 PAH concentrations were dominated by lower molecular weight PAHs (Fig.…”
Section: Ambient Concentrationssupporting
confidence: 90%
See 2 more Smart Citations
“…The PAH levels at the urban site determined in this study are comparable to those reported by Possanzini et al [30] for downtown Rome and by Halsall et al [31] for urban sites in London and Manchester. Because of their higher volatility, low to medium molecular weight PAHs (3-5 rings) were more abundant in the gas-phase in the present study, similar to the previous studies [24,[32][33][34]. Higher ambient PAH concentrations were measured in the gasphase and 14 PAH concentrations were dominated by lower molecular weight PAHs (Fig.…”
Section: Ambient Concentrationssupporting
confidence: 90%
“…The decrease in deposition velocity with increasing molecular weight is supported by other experimental studies which have shown that a greater fraction of the higher molecular weight PAHs are associated with fine particles relative to the lower molecular weight compounds [4,36,37]. A similar decrease in deposition velocity with increasing molecular weight was previously reported for PAHs [4,5,[33][34][35]38]. Table 3 shows the individual PAH concentrations in soils taken from the suburban site.…”
Section: Particle-phase Dry Deposition Fluxes and Velocitiessupporting
confidence: 81%
See 1 more Smart Citation
“…Details about these locations are presented elsewhere Sofuoglu et al, 1998;Franz et al, 1998). The dry deposition samples were collected with Eagle II automatic dry deposition collectors.…”
Section: Sampling Programmentioning
confidence: 99%
“…These plates are automatically covered when a moisture sensor detects rain or snow and exposed to the atmosphere during dry periods. The sampler is described in more detail elsewhere (Franz et al, 1998;Sofuoglu, 1996).…”
Section: Sampling Programmentioning
confidence: 99%